Is There Any Relationship between Human Herpesvirus-8 and Multiple Myeloma?. (26th February 2013) - Sadeghian, Mohammad Hadi; Mohammadnia Avval, Maryam; Ayatollahi, Hossein; Keramati, Mohammad Reza; Memar, Bahram; Amel Jamedar, Saeed; Sheikhi, Maryam; Shaghayegh, Gohar
Abstract : Background . Human herpesvirus-8 (HHV-8) is associated with some human diseases including Kaposi's sarcoma and also some B-cell lymphoproliferative disorders. Few studies have highlighted the potential role of HHV-8 in the development of multiple myeloma (MM) which is known as a malignant proliferation of plasma cells derived from a single clone. Aims . The aim of this study was to find a relationship between HHV-8 and MM using polymerase chain reaction (PCR) method. Materials and Methods . This study was conducted on 30 formalin-fixed, paraffin-embedded (FFPE) bone marrow biopsies of multiple myeloma and 30 normal FFPE bone marrow biopsies. After the sample preparation, Deoxyribonucleic acid (DNA) was extracted by nonheating procedure. PCR for HHV-8 virus was carried out with commercial kit and the PCR products were visualized by gel electrophoresis. Finally, the statistical analysis was performed. Results . HHV-8 virus was not detected by PCR from FFPE blocks of multiple myeloma samples, while only one of the controls showed DNA band of the corrected molecular weights. Fisher's exact test showed that no statistical differences were found between the two groups (P = 0.999 ). Conclusion . Our report adds to the body of evidence that there is no association between HHV- 8 and MM against a major role of HHV-8 infection in the pathogenesis of clonal plasma cell proliferation.